DiseÃ±o De Un Sistema De GestiÃ³n Integral Para El Manejo De Residuos SÃ³lidos En El Mercado â€œLa Mercedâ€ - Hannibal, Brito; Paulina, Robalino; Mayra, Espinoza; Fausto, Yaulema; Patricia, Freire; Natalia, Moreno; Berlis, GÃ³mez; Marcela, Inca (European Scientific Journal, ESJ, 2016)
An integral management system was designed to handle solid waste from â€œLa Mercedâ€ market in the city of Riobamba. For this purpose, a causeeffect relationship was established and an environmental diagnosis (base line) was made to know where the problem arose due to the mishandling of the solid waste. A random sampling was applied, which allowed it to know how many sample should be studied. The information was gathered in a seven day sampling period, March 16 -22 of 2015. The identification, characterization and quantification of the solid waste along with the identification of negative environmental impacts were carried out in order to pose alternative proposals for the integral management of the solid waste generated at this market. The results obtained showed an impact of moderate level (55%) with a mean of 550,38 kg/day. Profitable organic material was identified (85% plastic, 7% paper, 1% cardboard and 2% of other residuals). The calculated per capita production (PCP) was 0,18 kg/inhabitant/day. It is concluded that with the implementation of this research some of the environmental problems caused by the mishandling of the waste will diminish. It is recommended that the â€œManual of Integral Management of Solid Wasteâ€ be implemented in â€œla Mercedâ€ market, which will contribute to pose solutions that help to improve the quality of life of the population, promoting an ecologically proper management of the waste, from its generation to its final disposal.